2019
DOI: 10.3390/agriculture9050090
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Maize Farmers’ Adaptation Strategies to Climate Change and Variability in Ghana

Abstract: This study examined the adaptation strategies of maize farmers to climate change and variability in the Eastern Region of Ghana using primary data collected from 150 maize farming households by the administration of structured questionnaires. The results of the multinomial logit regression revealed that rainfall perception, access to credit, and farming experience significantly influenced the adoption of recommended agricultural practices, whereas the adoption of soil-related strategies is influenced by gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
(38 reference statements)
3
27
0
Order By: Relevance
“…The conceptualization of a globalized world, which is places connected and interdependent, explains how the local place phenomenon has global implications. For instance, place experiences such as harvest failures, low crop yields, poverty, malnutrition, reduced biological productivity, forest loss, continuous land degradation, reduction in livestock, loss of non-timber products, and the loss of arable lands for crop cultivation in rural Ghana are the externalities of global climate Philip Tetteh Quarshie Ph.D. Geography + International Development Studies, Department of Geography Environment and Geomatics, University of Guelph 7 | P a g e Email: pquarshi@uoguelph.ca|Twitter: @PhilipTQuarshi1 change (Asante & Amuakwa-Mensah, 2014;Sadiq et al, 2019). This place experience is considered to undermine global effort in tackling issues such as rural poverty and food insecurities (Dixon & Stringer, 2015;Fraser et al, 2016).…”
Section: Ecological Place Meaningmentioning
confidence: 99%
See 4 more Smart Citations
“…The conceptualization of a globalized world, which is places connected and interdependent, explains how the local place phenomenon has global implications. For instance, place experiences such as harvest failures, low crop yields, poverty, malnutrition, reduced biological productivity, forest loss, continuous land degradation, reduction in livestock, loss of non-timber products, and the loss of arable lands for crop cultivation in rural Ghana are the externalities of global climate Philip Tetteh Quarshie Ph.D. Geography + International Development Studies, Department of Geography Environment and Geomatics, University of Guelph 7 | P a g e Email: pquarshi@uoguelph.ca|Twitter: @PhilipTQuarshi1 change (Asante & Amuakwa-Mensah, 2014;Sadiq et al, 2019). This place experience is considered to undermine global effort in tackling issues such as rural poverty and food insecurities (Dixon & Stringer, 2015;Fraser et al, 2016).…”
Section: Ecological Place Meaningmentioning
confidence: 99%
“…For instance, in Ghana's semi-arid regions, farmers use the same piece of farmland to practice mixed crop farming, stone bonding, dry season farming using irrigation, and or turn to adopt improved seeds (Ahmed et al, 2016;Ndamani & Watanabe, 2016). Another place-based experience noted by (Antwi-Agyie et al, 2015;Kumasi et al, 2019;Wrigley-Asante et al, 2019;Sadiq et al, 2019) suggested that intensification by some smallholders involves the use of drought resistance variety crop, fertilizer application and efficient use of labour on that same piece of land.…”
Section: Agricultural Intensification 3 At Old Farm Locationmentioning
confidence: 99%
See 3 more Smart Citations